Paracoccidioides brasiliensis 87-Kilodalton Antigen, a Heat Shock Protein Useful in Diagnosis: Characterization, Purification, and Detection in Biopsy Material via Immunohistochemistry - Díez, Soraya (American Society for Microbiology, 2002)
The 87-kDa antigen derived from the fungal pathogen Paracoccidioides brasiliensis can be detected in the sera of infected patients, and its levels have been shown to correlate well with response to treatment and with clinical cure. Despite its potential importance, the antigen has been poorly characterized. The 87-kDa antigen was purified to homogeneity via preparative gel electrophoresis; N-terminal amino acid sequencing revealed substantial homology with heat shock proteins (hsps) from a variety of organisms. A monoclonal antibody (MAb) raised against a Histoplasma capsulatum 80-kDa hsp showed cross-reactivity to the purified 87-kDa antigen via Western blotting, and the 87-kDa-specific MAb P1B demonstrated that the antigen was expressed at higher levels in yeast than in mycelia by the same technique. Enzyme-linked immunosorbent assay and immunofluorescence reactivity using P1B confirmed increased expression of the 87-kDa antigen during the temperature-induced transformation of mycelia to yeast. Yeast-to-mycelium transformation was accompanied by a fall in expression, although the 87-kDa antigen was clearly constitutively expressed in both phases. Immunochemical staining of tissues from patients with MAb P1B who were infected with P. brasiliensis confirmed in vivo expression of the 87-kDa antigen by yeasts, and identification of this antigen via this method appears to be a useful adjunct to other methods used to diagnose paracoccidioidomycosis.